QUALITY OF CURED FISHERY PRODUCTS FROM MALABAR AND KANARA COASTS - JOSEPH, K GEORGE; MURALEEDHARAN, V; NAIR, T. S UNNIKRISHNAN (Fishery Technology, 2017)
Results of chemical, bacteriological and organoleptic quality studies of cured fisheryproducts of commerce collected from six major fish curing centres on the west coast of India are presented. 77.12% of the samples had moisture above 35%, 97.18% showed salt content below 25% and all samples had acid insoluble ash above 1.5%. 42.32% gave standard plate counts above 10,000 and 45.77% were contaminated with 'Red' halophiles. The major defects in curing were imperfect cleaning, inadequate salting and unhygienic conditions of processing